Terapi Relaksasi Benson Menurunkan Tekanan Darah pada Lansia Hipertensidi Panti Sosial Lanjut Usia (PSLU) Mandalika Mataram - Citra Sepriana; Chairun Nasirin; Perawati Sulastri; Agus Putradana (LPPM STIKES Mataram, 2023)
Introduction: Hypertension is a serious health problem for the elderly worldwide. The current therapy method continues to be developed into several methods, one of which is benson relaxation therapy. This therapy focuses on certain phrases that are repeated using a regular rhythm accompanied by submissive and orderly behavior. Purpuse: determine the effect of benson’s relaxation therapy on reducing blood pressure, especially in the elderly who suffer from high blood pressure in Mataram mandalika elderly social institutions (PSLU). Methods: The research design used in this study was experimental with a one-group pretest-posttest design approach. The population in this study were all elderly people who experienced hypertension at the Mataram mandalika elderly social institution. The sampling technique in this study was total sampling. The research instrument used SOP for benson relaxation therapy and used a blood pressure meter and stethoscope to measure blood pressure. This therapy was carried out 2 times a day (morning and evening) for days for 5-10 minutes. Data analysis using pained hest test. Result: that 13 people (62%) had blood pressure before being given benson relaxation therapy. The results of blood pressure after being given benson relaxation therapy decreased blood pressure in stage I in as many as 21 people (100%). The paired t-test statistical test results obtained a significant number or a Sig (2-Tailed) value of 0.000, which means <0.05. Conclusion: that there is an effect of benson relaxation therapy on reducing blood pressure in elderly people with hypertension at the Mataram mandalika social institution.